Rapidly progressive glomerulonephritis as an unusual type of renal involvement in sarcoidosis: a case report - K. Graňák; M. Vnučák; P. Kleinová; T. Blichová; A. Kollár; I. Dedinská (Journal of Medical Case Reports)
Abstract Introduction Sarcoidosis is a multisystem inflammatory disease of unknown etiology characterized by the formation of noncaseating epithelioid granulomas. Clinically significant renal involvement is rare in sarcoidosis. It most commonly manifests as chronic tubulointerstitial nephritis and nephrocalcinosis with nephrolithiasis. Further, glomerular involvement is observed sporadically, mainly membranous glomerulopathy or focal segmental glomerulosclerosis. Case presentation We describe the clinical case of a 49-year-old patient of Caucasian ethnicity with a history of sarcoidosis of the lungs and intrathoracic lymph nodes who was hospitalized for acute kidney injury, hypercalcemia, hypoxemic respiratory insufficiency, general weakness, weight loss, and fever. Conservative treatment was not successful, and therefore early initiation of renal function replacement in the form of intermittent hemodialysis was necessary. During differential diagnosis process, we found nephrotic range proteinuria with microscopic hematuria; autoantibody panel was completely negative. Histologically, a unique constellation of renal lesions in the form of severe chronic tubulointerstitial nephritis combined with diffuse sclerosing crescentic glomerulonephritis was confirmed. Computed tomography scan of the lungs revealed recurrence of sarcoidosis, and a secondary finding was subpleurally localized primary calcified tuberculous infection. Treatment with corticosteroids was initiated in collaboration with a pulmonologist, with rapid improvement in the patient’s extrarenal clinical condition. Conclusion Sarcoidosis needs to be considered in the differential diagnosis of rapidly progressive glomerulonephritis even though it is a very rare type of renal involvement.